PENERAPAN PENDIDIKAN FINANCIAL PADA ANAK USIA SEKOLAH - abdillah mundir (Al-Mudarris: Journal Of Education, 2018)
A child's intelligence cannot only be measured by academic intelligence at school. Children's intelligence in regulating emotions, intelligence interacting in the social environment and also intelligence in managing finances are also part of a child's intelligence. To hone the financial intelligence of a child, it should begin to grow early, namely from the age of school to become a living culture in their daily lives. The success of the Indonesian economy is our success in preparing our children to prepare their future economies.